APPROACHMENT AND MANAGEMENT GAME ADDICTION AS CLINICAL CONDITION - Ratri Istiqomah (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2020)
Online games phenomenon that occur in Indonesia arises after internet access became easily as well as globalization around the world. Ignorance of problems that may arise quite late to realize that causing addiction problems due to the game has worldwide. In 2000 the number of Internet users in Indonesia reached two million people, this number increased to 71.190 million in 2014. When the game created an addiction condition, the game changed the balance in the neurotransmitters of the brain that play a role in the reward system, which would eventually change the structure of the nervous system anatomically and have an effect on changes in the regulation of emotions, cognition, and psychomotor. Clinical manifestations observed in a person with addiction games in the form of preoccupation in games; lying or hiding reality about the usual game; loss of interest and interest in other activities; withdrawal from social life; defensive and irritable. Treatment modalities that can be done include limiting screen time, support from parents or family, resting eyes and muscles, changing to educational games, diverting to more useful activities, academic guidance, family therapy, and comprehensive referral system should be made if the condition was permitted.Keywords: game, addiction, internet.